Recria e Terminação de Bovinos Machos Inteiros e Imunocastrados de Dois Grupos Genéticos. - Cunha, Maryanne Silva (Universidade Federal do Tocantins, 2023)
The aim of this study was to evaluate the effect of immunocastration of Nellore male and Holstein-Zebu cattle receiving supplement at a rate of 1 and 2% of body weight during the growing and finishing phases, respectively. Thirty-six male cattle (217.80 ± 20.58 kg) were distributed following a completely randomized design with a 2 × 2 factorial arrangement into two genetic groups (Nellore and Holstein-Zebu) and two sex classes (intact and immunocastrated). Immunocastration reduced the circumference, width, length, weight and volume of the testicles. The average daily weight gain (DWG) of the intact and immunocastrated animals was similar during the growing phase, but at the finishing phase the DWG was higher for the intact animals. The genetic groups did not altered DWG and the hot carcass weight and cold carcass weight, however Nellore animals showed higher hot carcass yield and cold carcass yield. The glucose, creatinine and aspartate aminotransferase concentrations were higher for the Nellore during growth. The urea concentration showed interaction between the genetic groups and the sexual conditions at finishing. Immunocastration increased the subcutaneous fat thickness (SFT) in the Holstein-Zebu, but had no effect on SFT in Nellore animals. The intact males had larger Longissimus lumborum area, muscle proportion and forequarter. On the other hand, the immunocastrated males had fat in carcass and meat higher and shear force of meat lower, lightness (L*), redness (a*) and yellowness (b*) of meat and b* of fat higher. Male dairy cattle show performance, carcass and meat characteristics similar to that of Nellore males and can be used for beef production, but their carcass yield is lower. Immunocastration reduces performance, as a result termination of intact males is more economically viable. However, the immunocastration increases the fat in the carcass, the tenderness and improves the visual aspects meat. Therefore, the immunocastration should only be used when a differentiated payment exists for castrated animals at slaughter.